2016
DOI: 10.1007/s00285-016-1073-6
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical analysis of rebound in a target-mediated drug disposition model: II. With feedback

Abstract: We consider the possibility of free receptor (antigen/cytokine) levels rebounding to higher than the baseline level after the application of an antibody drug using a target-mediated drug disposition model. It is assumed that the receptor synthesis rate experiences homeostatic feedback from the receptor levels. It is shown for a very fast feedback response, that the occurrence of rebound is determined by the ratio of the elimination rates, in a very similar way as for no feedback. However, for a slow feedback r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The parameters that affected rebound were also mathematically analyzed by Aston et al . (see Figure ).…”
Section: One‐compartment Modelmentioning
confidence: 99%
“…The parameters that affected rebound were also mathematically analyzed by Aston et al . (see Figure ).…”
Section: One‐compartment Modelmentioning
confidence: 99%
“…Towards this goal, assays have been established to study inhibition reversibility [9]. It is generally accepted that response to irreversible inhibitors are time-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…They can be served as a useful theoretical framework. Model-based analysis revealed that the necessary and sufficient condition for receptor rebound in a single dose animal experiment is that elimination rate of the drug-receptor product being slower than the elimination rates of the drug and of the receptor [9]. A time-scale analysis was also performed to provide accurate approximations of the temporal evolution under the assumption of high drug binding affinity [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation